Effects of conflict on resistance and cooperation in hierarchical groups - Hristov, H (2019)
Many social organisms engage in collective actions in which there is a mismatch between individual and common interest. Such problems may include competition with other groups or collaborative efforts to secure resources from the environment. In this thesis I test novel theoretical predictions which see hierarchy as one potential solution to the collective action problem at hand. More specifically, models have shown that high-rank individuals in hierarchical groups are expected to contribute more toward the group’s success than low-rank individuals during inter-group conflict. This pattern of contribution by the high-rank group members is expected to increase the group effort of hierarchical groups in comparison to egalitarian groups. However, the increased individual effort of high-rank individuals is expected to reduce their net benefits in comparison to individuals with lower rank.